PENGARUH AUDIT TENURE, ROTASI AUDIT, AUDIT FEE, DAN AUDIT DELAY TERHADAP KUALITAS AUDIT (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Rini Hafiztri; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2026)
This study analyze the effects of audit tenure, audit rotation, audit fee, and audit delay on audit quality for companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. This study refers to agency theory.The population for this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Purposive sampling was used to select the research sample, resulting in 294 research samples for three consecutive years (2022–2024). The data used are secondary data obtained from the financial statements and independent auditor reports of companies in the manufacturing sector listed on the Indonesia Stock Exchange (IDX). Data analysis was performed using multiple linear regression with SPSS 30 software.The results of the analysis indicate that audit tenure and audit delay have a negative and significant effect on audit quality, while audit rotation and audit fee have a positive and significant effect on audit quality.